Jom Berkhemah: A 3D Desktop Game - Ikmal, Muhammad; Md. Fudzee, Mohd Farhan (Applied Information Technology And Computer Science, 2025)
Many young people, especially those who live in the cities, do not know basic survival skills like finding food, cleaning water, or building shelters. Learning from books, videos, or even short survival courses is not enough to give people the real experience they need to survive in the wild. Jom Berkhemah helped teach these survival skills in a fun and interactive way. The game is for targeted audiences aged 12 to 18 and uses the Game Development Life Cycle (GDLC) method, which includes steps like initiation, pre-production, production, testing, beta, and release phase. Players can try out real survival activities, such as crafting tools or finding food, inventory management while also keeping track of things like hunger and energy levels. GDLC methodology was used in developing the game before applying System Usable Scale (SUS) to evaluate functionality of the game. The game achieved a SUS score of 85.75, which was considered excellent in testing. By implementing the 3D Survival gameplay, the game hopes to give some knowledge about the survival’s skills for emergency matter and learn in the most exciting way